2012
DOI: 10.1590/s0103-64402012000400014
|View full text |Cite
|
Sign up to set email alerts
|

In situ evaluation of orthodontic elastomeric chains

Abstract: The hypothesis tested in this study was that intraoral exposure of elastomeric chains alters their tensile strength. For such purpose, it was evaluated the in situ behavior of different elastomeric chains stretched for 3 weeks. Three kinds of elastomeric chains, Plastic chain (PC), Memory chain (MC) and Super slick chain (SSC), were randomly placed in 3 quadrants of 13 patient in a fixed distance of 16 mm and mean initial force of 180 g. Tensile testing was performed in an universal testing machine at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
(34 reference statements)
2
11
1
5
Order By: Relevance
“…Baratieri et al (23) (2012) tested whether intraoral exposure of elastomeric chains alters their tensile strength or not. 3 kinds of elastomeric chains, Plastic chain (PC), Memory chain (MC) and Super slick chain (SSC), were randomly placed in 3 quadrants of 13 patient and stretched for 3 weeks.…”
Section: In-vivo Effectmentioning
confidence: 99%
“…Baratieri et al (23) (2012) tested whether intraoral exposure of elastomeric chains alters their tensile strength or not. 3 kinds of elastomeric chains, Plastic chain (PC), Memory chain (MC) and Super slick chain (SSC), were randomly placed in 3 quadrants of 13 patient and stretched for 3 weeks.…”
Section: In-vivo Effectmentioning
confidence: 99%
“…When they are distended around brackets, they lose force over time. Their properties undergo changes, and one of these is force degradation when they are subjected to traction, resulting the their gradual loss of effectiveness 9 . Various studies with chain elastics have shown that these materials cannot produce constant levels of force for a long period of time, and the greatest the reduction in their force occurs in the first few hours 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of elastomeric chains, indicated for the correction of rotations and space closures in orthodontics, began in the 1960s [3][4][5] . Nevertheless, in spite of the important role of force transmission, they are still not considered ideal materials because they present a relevant decline in force that may cause a clinical problem, since orthodontic treatments act on the basis of the force of these accessories.…”
Section: Introductionmentioning
confidence: 99%